Interaction between the long-tailed macaque and the dung beetle in Langkawi - Muhaimin, A. M. D.; N. R., Aifat; M. A. B., Abdul-Latiff; B. M., Md. Zain; S., Yaakop (Universiti Putra Malaysia Press, 2017)
The interaction between dung beetles and primates was studied at Telaga Tujuh, Langkawi Island, Malaysia using such as observation and sampling method. The dung beetles were caught, and their dung balls collected. The beetles were identified as Paragymnopleurus maurus, and their dung balls were identified as originating from Macaca fascicularis, using a molecular approach involving the cytochrome b (Cytb) marker. This is the first record of Paragymnopleurus maurus from the study site in the Langkawi Islands and from this part of Malaysia. Paragymnopleurus maurus is attracted to the omnivorous dung of M. fascicularis, because it is a preferred food source for the beetle. Daytime is the active period for P. maurus and this study shows that the foraging area of P. maurus is restricted to the forest, even though the beetle’s food source (M. fascicularis’s dung) can be found outside the forest.